European Migration to the United States: An Econometric Analysis of Aggregate Labor Supply and Demand - Wilkinson, Maurice (The Review of Economics and Statistics, 1970)
Maurice Wilkinson, European Migration to the United States: An Econometric Analysis of Aggregate Labor Supply and Demand, The Review of Economics and Statistics, Vol. 52, No. 3 (Aug., 1970), pp. 272-279